(untitled) (Лучшие интеллектуальные исследования, 2024)
Annotation: This article discusses media literacy, social networks, risks of their use, important aspects of the field, information filtering skills, the harmful impact of mass media, the development of social networks influencing sociopolitical changes in society, understanding media functions, the main advantages of using social networks in society, information with nationalist and local sentiments, and the promotion of mass culture.